Analysis of Value Added and Contribution of Broom Craft Business to Household Income (Case Study of Kajongan Village, Purbalingga Regency) - Sultan Ahmad Ivana Jasetra; Neni Widayaningsih (Jurusan Ilmu Ekonomi dan Studi Pembangunan Universitas Jenderal Soedirman, 2022)
This research was conducted in Kajongan Village, Purbalingga Regency. This study aims to analyze the value added and contribution of the broom craft business to the household income of entrepreneurs in a period of one year. The types of brooms that were studied are gelagah brooms, ijuk brooms, and hamada (brooms made from wheat plants). Respondents in this study amounted to 34 broom entrepreneurs. Data collection techniques were carried out through questionnaires and interviews. The analytical method used is the hayami method value added analysis and income contribution analysis. This study is a development from previous research that uses the Hayami method to analyze the value added from craft products. Based on the results of the study, it can be concluded that the highest value added ratio is produced by the production of hamada brooms. Then the second highest is produced from the production of ijuk brooms. The production of gelagah brooms contributes the lowest value added and value added ratio. Meanwhile, the largest to the smallest income contribution was generated from the production of hamada brooms, gelagah brooms, and ijuk brooms, respectively. The implication is that entrepreneurs need to choose the best raw materials and provide innovations to improve product quality so that the value added can be increased. In addition, entrepreneurs need to expand the market so that the number of sales can be increased. In the end, this will have an impact on increasing the household income of entrepreneurs.Keywords: Value Added Craft, Broom Craft, Income Contribution